2016
DOI: 10.1007/s11060-016-2226-6
|View full text |Cite
|
Sign up to set email alerts
|

hTERT promoter methylation in meningiomas and central nervous hemangiopericytomas

Abstract: In meningiomas, prognostic impact of mutations in the human telomerase reverse transcriptase (hTERT) promoter region was recently shown, while studies of promoter methylation and analyses of hemangiopericytomas are lacking. hTERT promoter methylation was analyzed in 78 meningioma and 38 meningeal hemangiopericytoma samples by methylation-specific polymerase chain reaction (MS-PCR) and compared with histopathological and clinical variables and with immunohistochemical hTERT expression. Promoter methylation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…4,12,40,41 Corresponding data have been reported 1592 Spiegl-Kreinecker et al TERT promoter alterations of meningiomas for meningiomas, where TERT promoter methylation was associated with increasing tumor grade and upregulation of TERT mRNA expression. 13 In the latter study, a minor but significant impact of TERT promoter methylation on patient OS was detected in univariate analysis, which, however, lost significance in the multivariate setting. In our study, we have analyzed TERT promoter methylation in all TERTp-mut meningioma compared with a selection of TERTp-wt tumors positive and negative for telomerase reactivation.…”
Section: Neuro-oncologymentioning
confidence: 84%
See 2 more Smart Citations
“…4,12,40,41 Corresponding data have been reported 1592 Spiegl-Kreinecker et al TERT promoter alterations of meningiomas for meningiomas, where TERT promoter methylation was associated with increasing tumor grade and upregulation of TERT mRNA expression. 13 In the latter study, a minor but significant impact of TERT promoter methylation on patient OS was detected in univariate analysis, which, however, lost significance in the multivariate setting. In our study, we have analyzed TERT promoter methylation in all TERTp-mut meningioma compared with a selection of TERTp-wt tumors positive and negative for telomerase reactivation.…”
Section: Neuro-oncologymentioning
confidence: 84%
“…This clearly indicates that TERT promoter mutation rather than methylation dominates telomerase activation in anaplastic meningiomas. In contrast, Furtjes et al 13 suggested enhanced TERT protein expression in methylated cases based on immunohistochemistry. This could be due to the different methods used for detection of TERT promoter methylation (methylation-specific PCR versus pyrosequencing) and gene expression (RT-PCR and telomeric repeat amplification protocol [TRAP] assay versus immunohistochemistry).…”
Section: Neuro-oncologymentioning
confidence: 94%
See 1 more Smart Citation
“…9 Multiple independent groups have shown that TERT promoter mutations are associated with shorter time to recurrence, survival, and overall poor prognosis. 2,12,13,25 In addition to somatic mutations, specific DNA methylation patterns have recently been discovered that complement known chromosomal rearrangements that are associated with tumor grade and survival. 4,26 In contrast to mechanisms occurring within the meningioma, another possibility is that the immune environment and tumor-immune system interaction may alter tumor growth and drive the development of large size.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…THOR was further explored in prostate cancer and has shown its role as a potential marker with diagnostic and prognostic properties [ 139 ]. These findings have been expanded upon by multiple groups implicating h TERT promoter methylation in h TERT upregulation, and further demonstrating not only its diagnostic but, importantly, its clinical significance in cancer prognostic including thyroid cancer, acute myeloid leukemia/myelodisplastic syndrome, esophageal carcinoma, meningioma, pituitary adenomas, colorectal cancer and hepatocellular carcinoma) [ 72 , 82 , 139 , 152 157 ]. In these studies, h TERT promoter hypermethylation was positively correlated with high h TERT expression, telomerase reactivation and in the vast majority of the cases correlated with worse clinical outcomes.…”
Section: Introductionmentioning
confidence: 96%